2014
DOI: 10.1270/jsbbs.64.351
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs controlling harvest time and fruit skin color in Japanese pear (Pyrus pyrifolia Nakai)

Abstract: Using an F1 population from a cross between Japanese pear (Pyrus pyrifolia Nakai) cultivars ‘Akiakari’ and ‘Taihaku’, we performed quantitative trait locus (QTL) analysis of seven fruit traits (harvest time, fruit skin color, flesh firmness, fruit weight, acid content, total soluble solids content, and preharvest fruit drop). The constructed simple sequence repeat-based genetic linkage map of ‘Akiakari’ consisted of 208 loci and spanned 799 cM; that of ‘Taihaku’ consisted of 275 loci and spanned 1039 cM. Out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 39 publications
4
61
0
Order By: Relevance
“…The potential of GWAS was examined in pear with a population of 76 Japanese pear cultivars: significant associations detected in the GWAS agreed well with the results of biparental linkage/QTL mapping (Iwata, Hayashi, Terakami, Takada, Sawamura et al, 2013). Two significant associations of marker genotypes with harvest time detected in GWAS were also detected in biparental QTL mapping (Yamamoto et al, 2014). A significant association of marker genotypes with resistance to black spot disease was located close to the disease susceptibility genes Ani and Ana, which had been detected in biparental linkage mapping (Terakami et al, 2007).…”
Section: Genome-wide Association Studiessupporting
confidence: 56%
See 2 more Smart Citations
“…The potential of GWAS was examined in pear with a population of 76 Japanese pear cultivars: significant associations detected in the GWAS agreed well with the results of biparental linkage/QTL mapping (Iwata, Hayashi, Terakami, Takada, Sawamura et al, 2013). Two significant associations of marker genotypes with harvest time detected in GWAS were also detected in biparental QTL mapping (Yamamoto et al, 2014). A significant association of marker genotypes with resistance to black spot disease was located close to the disease susceptibility genes Ani and Ana, which had been detected in biparental linkage mapping (Terakami et al, 2007).…”
Section: Genome-wide Association Studiessupporting
confidence: 56%
“…A significant association of marker genotypes with resistance to black spot disease was located close to the disease susceptibility genes Ani and Ana, which had been detected in biparental linkage mapping (Terakami et al, 2007). The results of GWAS and biparental mapping also agreed in fruit skin colour (Yamamoto et al, 2014). These results suggest that GWAS will be useful for the detection of QTLs for important agronomic traits, and will provide an effective alternative to the traditional time-consuming QTL mapping.…”
Section: Genome-wide Association Studiesmentioning
confidence: 56%
See 1 more Smart Citation
“…In the middle of LG-D, significant QTLs (qtl-HARVESTKu-D and qtl-HARVEST-T43-D) were detected in both the Kx709 and Px43 populations, and their LOD scores and percentages of phenotypic variance explained were similar, suggesting that these QTLs were controlled by the same gene and probably had high reliability and general versatility. Many QTLs for fruit harvesting day have been identified in several fruit tree species (Eduardo et al, 2011;Kenis et al, 2008;Kunihisa et al, 2014;Liebhard et al, 2003;Yamamoto et al, 2014), and broad-sense heritability of fruit harvesting day was higher than that of other fruit traits Nishio et al, 2014;Yamada et al, 1993). Thus, both the QTLs for fruit harvesting day identified in earlier studies and the HARVEST QTLs identified here may have been identified owing to their high heritability.…”
mentioning
confidence: 99%
“…However, GWASs are just beginning to be applied to fruit tree species, with only a few species having being analyzed to date (Myles et al 2011). Yamamoto et al (2014) conducted GWASs to detect significant associations between 162 markers and nine agronomic traits, including harvest time, resistance to black spot disease, firmness of flesh, fruit size, fruit shape in the longitudinal section, acid content, total soluble solid content, number of spurs, and tree vigor, which are important in pear production. GWASs using the 76 Japanese pear cultivars have detected four markers showing significant associations with three traits: resistance to black spot disease, harvest time, and the number of spurs.…”
Section: Genome-wide Association Studies (Gwass) In Pyrusmentioning
confidence: 99%